Civil justice, privatization, and democracy - Farrow, Trevor C. W (University of Toronto Press, 2014)
Civil Justice, Privatization, and Democracy demonstrates the urgent need to publicize, politicize, debate, and ultimately temper these moves towards privatized justice.